2015
DOI: 10.1097/jto.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis Trumps T Stage and Proposed International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society Classification for Prognostic Value in Resected Stage 1 Lung Adenocarcinoma

Abstract: In this study of resected stage 1 primary lung adenocarcinoma, we found mitotic index to be the only independent prognostic marker. It was more closely associated with outcome than either pathologic T stage or IASLC/ATS/ERS architecture-based classification. Further validation of concordance and reproducibility in reporting mitotic index, as well as validation of prognostic significance, needs to be undertaken in independent data sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…31,32 However, it would be useful to stratify further the intermediate-grade acinar and papillary adenocarcinomas, and this may be a good role for nuclear grading and mitotic counts. [27][28][29]33,34 However, more investigation is needed to address which approach is clinically relevant. For resected squamous cell carcinomas, there is very little data available, but nuclear diameter has been shown to be an independent predictor of worse outcome.…”
Section: Histologic Grading Of Lung Cancermentioning
confidence: 99%
“…31,32 However, it would be useful to stratify further the intermediate-grade acinar and papillary adenocarcinomas, and this may be a good role for nuclear grading and mitotic counts. [27][28][29]33,34 However, more investigation is needed to address which approach is clinically relevant. For resected squamous cell carcinomas, there is very little data available, but nuclear diameter has been shown to be an independent predictor of worse outcome.…”
Section: Histologic Grading Of Lung Cancermentioning
confidence: 99%
“…DUHIG et al [28] examined 145 stage I adenocarcinomas and found that lepidic adenocarcinoma had 100% survival, with survival for acinar/papillary and solid adenocarcinomas of 70% and 55%, respectively. These authors concluded that mitotic count was the best stratifier, even within solid, acinar and papillary subtypes.…”
Section: Stage 1 Adenocarcinomamentioning
confidence: 99%
“…Also, Kadota et al demonstrated a significant association of mitotic count with histology grade, Ki‐67 proliferative index, and recurrence‐free probability, and concluded that mitotic count was the single most important predictor of recurrence in patients with stage 1 lung adenocarcinoma . In another study, Duhig et al suggested that mitotic index is the only independent prognostic marker for patients who have undergone resection for stage I lung adenocarcinoma …”
Section: Discussionmentioning
confidence: 99%